2013
DOI: 10.3109/00952990.2013.843005
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive, psychological and behavioral correlates of binge drinking and use of alcohol with caffeinated beverages in college-aged adults

Abstract: Overall, these data suggest that binge drinking and AmCB use are associated with P3 alterations, but the specific effects may differ for individuals with different patterns of risky alcohol use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
(51 reference statements)
0
11
1
4
Order By: Relevance
“…differences in these electrophysiological components linked to inhibition and execution responses (Watson et al, 2014(Watson et al, , 2016. The present study also failed to find differences in Go-and NoGo-P3 responses, i.e., these components seemed not to be significantly affected by BD, which is contrary to what was observed in a previous study from our laboratory with a different sample (López-Caneda et al, 2012).…”
Section: Discussioncontrasting
confidence: 99%
“…differences in these electrophysiological components linked to inhibition and execution responses (Watson et al, 2014(Watson et al, , 2016. The present study also failed to find differences in Go-and NoGo-P3 responses, i.e., these components seemed not to be significantly affected by BD, which is contrary to what was observed in a previous study from our laboratory with a different sample (López-Caneda et al, 2012).…”
Section: Discussioncontrasting
confidence: 99%
“…However, two studies did not observe such a deficit in heavy social drinkers (Adams et al, 2013;Nederkoorn et al, 2009), whereas detoxified alcohol-dependent patients showed impaired response inhibition towards alcohol-related cues after 19.7 (±2.7) days of abstinence (Noël et al, 2007). However, several ERP studies revealed early cerebral dysfunctions related to alcohol consumption before any detectable behavioral impairment in social drinkers (Bijl et al, 2005;Nichols and Martin, 1996;Oddy and Barry, 2009), and in binge drinkers (López-Caneda et al, 2013Maurage et al, 2009Maurage et al, , 2012Watson et al, 2014). To our knowledge, only one electrophysiological study assessed the inhibition abilities toward alcohol-related information (Petit et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Although comparatively much less studied, electrophysiological measures of brain activity also appear to be sensitive to the BD pattern (López-Caneda et al, 2014a ; Petit et al, 2014b ). As such, anomalous brain responses have been documented in BD youths during cognitive tasks using event-related potentials (ERPs) and event-related oscillations (EROs; Crego et al, 2009 ; Maurage et al, 2012 ; Smith and Mattick, 2013 ; Petit et al, 2014a ; Watson et al, 2014 ; López-Caneda et al, 2017 ). Despite its well documented potential for detecting neurofunctional anomalies in chronic alcoholics, brain activity during task-free resting states has been virtually unaddressed in the BD population.…”
Section: Introductionmentioning
confidence: 99%